2017
DOI: 10.4103/ijem.ijem_529_16
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin B12 levels in type 2 diabetes patients on metformin compared to those never on metformin: A cross-sectional study

Abstract: Context:There are limited data about the effect of metformin use on serum Vitamin B12 levels in type 2 diabetes patients from India.Aims:We studied serum Vitamin B12 levels in patients with type 2 diabetes mellitus who were receiving metformin and compared them to those never treated with metformin.Subjects and Methods:A total of 183 patients (“metformin” group 121, “no metformin” group 63) of type 2 diabetes from the endocrinology clinic of a tertiary care center in North India were studied. Serum Vitamin B12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…This study suggests that vitamin B12 deficiency is highly prevalent in our population (7% of patients); however, it is not as high as described in some recent studies showing prevalence from 28 to 41% (18, 19, 20, 21). A recently published meta-analysis found that the use of metformin is a risk factor for vitamin B12 deficiency in diabetic patients (22).…”
Section: Discussionsupporting
confidence: 45%
“…This study suggests that vitamin B12 deficiency is highly prevalent in our population (7% of patients); however, it is not as high as described in some recent studies showing prevalence from 28 to 41% (18, 19, 20, 21). A recently published meta-analysis found that the use of metformin is a risk factor for vitamin B12 deficiency in diabetic patients (22).…”
Section: Discussionsupporting
confidence: 45%
“…reported no difference between vitamin B12 levels in people with diabetes taking metformin or without it. [20] Serum Vitamin B12 levels were 267.7 ± 194.4 pmol/l in metformin group and 275.1 ± 197.2 pmol/l in the no metformin group ( P = 0.78). [20] In current study, almost all patients enrolled with diabetes were on metformin and therefore no comparison could be done to delineate effect of metformin.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Serum Vitamin B12 levels were 267.7 ± 194.4 pmol/l in metformin group and 275.1 ± 197.2 pmol/l in the no metformin group ( P = 0.78). [20] In current study, almost all patients enrolled with diabetes were on metformin and therefore no comparison could be done to delineate effect of metformin. Discrepancy between Indian and western literature may be due to huge difference in prevalence of vitamin B12 deficiency among general population.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Raizada et al, no significant increase in the prevalence of neuropathy was found in vitamin B12-deficient patients compared with patients with normal vitamin B12 levels. They emphasized that the increased the duration of diabetes was associated with the severity of vitamin B12 deficiency [ 13 ].…”
Section: Discussionmentioning
confidence: 99%